1990
DOI: 10.1037/0022-006x.58.3.352
|View full text |Cite
|
Sign up to set email alerts
|

Mode-specific effects among three treatments for depression.

Abstract: In the NIMH Treatment of Depression Collaborative Research Program (TDCRP), 250 depressed outpatients were randomly assigned to interpersonal psychotherapy, cognitive-behavioral therapy, imipramine plus clinical management, or pill placebo plus clinical management treatments. Although all treatments demonstrated significant symptom reduction with few differences in general outcomes, an important question concerned possible effects specific to each treatment. The therapies differ in rationale and procedures, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
222
0
6

Year Published

1997
1997
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 287 publications
(248 citation statements)
references
References 23 publications
20
222
0
6
Order By: Relevance
“…The DAS consists of 40 statements to which patients respond on a 7-point scale ranging from 1 (totally agree) to 7 (totally disagree). For the current study, scores for the 11-item Need for Social Approval subscale (DAS-Approval; Imber et al, 1990; details provided by P. A. Pilkonis, personal communication, December 26, 2003) were used in analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The DAS consists of 40 statements to which patients respond on a 7-point scale ranging from 1 (totally agree) to 7 (totally disagree). For the current study, scores for the 11-item Need for Social Approval subscale (DAS-Approval; Imber et al, 1990; details provided by P. A. Pilkonis, personal communication, December 26, 2003) were used in analyses.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, reductions in negative cognitive products (i.e., the surface-level thoughts or dysfunctional attitudes) do not appear to be the mechanism by which CBT produces its results, as reductions in these thoughts have tended to covary with reductions in depression symptoms, occur in response to noncognitive treatments such as ADM therapy and interpersonal psychotherapy, and show little association with the durability of the treatment gains (cf. Hollon et al, 1992;Hollon & Kriss, 1984;Imber et al, 1990;Safran, Vallis, Segal, & Shaw, 1986;Simons, Garfield, & Murphy, 1984). Rather, changes in cognitive structures, core schema, or core processes are regarded as representing critical change mechanisms in cognitive therapy (Beck, Rush, Shaw, & Emery, 1979;Safran et al, 1986).…”
mentioning
confidence: 99%
“…However, this was nothing unique to CBT but has also been found to occur during a Mindfulness-Based Cognitive Therapy (MBCT) [66]. Moreover, it has been shown that during CBT as well as during ADM automatic negative thoughts decrease and this reduction in turn has been associated with overall clinical improvement, so as to patients who did not benefit from either intervention showed significantly less change on cognitive measures [67][68]. Further studies have confirmed that reductions in negative cognitions are not only present in CBT but that different CBT treatment components are comparably effective in reducing negative cognitions.…”
Section: The Mediating Role Of Cognitive Changesmentioning
confidence: 99%